2018
DOI: 10.5578/fmbd.66546
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and Theoretical Studies on Theobromine and Theobromine-Water Complexes

Abstract: In this study, the solvent effects on structural, spectroscopic, electronic and thermochemical properties of Theobromine (tbH) were theoretically investigated. The dichloromethane (DCM), dimethylsulfoxide (DMSO) and water (H2O) solvents have been chosen for investigations. Optimized molecular structures of tbH were obtained by using the DFT/B3LYP method with 6-311++G(d,p) basis set in vacuum and in solvent media. Calculated geometric structure parameters were compared with experimental data. In the experimenta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
4
3

Year Published

2020
2020
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(11 citation statements)
references
References 21 publications
4
4
3
Order By: Relevance
“…We noticed that the single C1–C4 bond length is shorter than the C1–C2 double bond length. The calculated C–N bond lengths were in better accord with the experimental data given in literature (Ford et al 1998 ; Bilkan 2018 ) compared to the other bond length. Similarly, the C–C–C, C–N–C O–C–N, N–C-N and C–C–O bond angles of Theobromine are approximately equal to experimental values given in literature (Ford et al 1998 ) compared to the theoretical values reported in literature (Bilkan 2018 ).…”
Section: Resultssupporting
confidence: 87%
See 4 more Smart Citations
“…We noticed that the single C1–C4 bond length is shorter than the C1–C2 double bond length. The calculated C–N bond lengths were in better accord with the experimental data given in literature (Ford et al 1998 ; Bilkan 2018 ) compared to the other bond length. Similarly, the C–C–C, C–N–C O–C–N, N–C-N and C–C–O bond angles of Theobromine are approximately equal to experimental values given in literature (Ford et al 1998 ) compared to the theoretical values reported in literature (Bilkan 2018 ).…”
Section: Resultssupporting
confidence: 87%
“…The E g values obtained from our studies eventually explains the charge transfer interactions taking place within Theophylline and Theobromine which is in line as reported in literature (Kadhum et al 2012 ). The E g value of Theobromine obtained is less than the theoretical values reported in literature (Bilkan 2018 ) which may be due to difference in basis set. The E g values obtained at the B3LYP level for both molecules are smaller than those obtained at the RHF and wB97XD.…”
Section: Resultscontrasting
confidence: 77%
See 3 more Smart Citations